If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -6(3x + 8) = 9 Reorder the terms: 4 + -6(8 + 3x) = 9 4 + (8 * -6 + 3x * -6) = 9 4 + (-48 + -18x) = 9 Combine like terms: 4 + -48 = -44 -44 + -18x = 9 Solving -44 + -18x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '44' to each side of the equation. -44 + 44 + -18x = 9 + 44 Combine like terms: -44 + 44 = 0 0 + -18x = 9 + 44 -18x = 9 + 44 Combine like terms: 9 + 44 = 53 -18x = 53 Divide each side by '-18'. x = -2.944444444 Simplifying x = -2.944444444
| 4a-9ifa=4 | | 2b-3-9b-8= | | -6-3n=12 | | 10x+60=140 | | 6-8x=58 | | 3a^2-4ab= | | 7x+15=5x+9 | | 10=4a-2 | | 3x(4)+4=23 | | 9c-6=2c+57 | | -5+4x+3x=-11 | | 7-3z+8z^2-8+4z= | | 9(e-2)=72 | | 4(3x)=84 | | 6(n+4)=-(2n-8) | | 3(x+1.8)=2(x-1.2) | | 100=b+72 | | 100=b+41 | | b+3a=4c | | 0.3x-0.3(3-x)=2.4 | | 6t+9+(-6)=15 | | 6m+6=2m+30 | | 3x+3z=5+8y | | 8(x+1)=4x-1 | | 3(x+1.8)=(X-1.2) | | 5+10x=9x+10 | | -4+2(3+x)=-14 | | y+73= | | 2t+8=-4(t-1) | | 5+(3*n)=5 | | 2s-13s=66 | | 7(4x)=89 |